Entrapment of an ACE inhibitory peptide into ferritin nanoparticles coated with sodium deoxycholate: Improved chemical stability and intestinal absorption. (July 2021) - Li, Ying; Zhang, Yunchen; Chai, Zhi; Huang, Wuyang; Cui, Li; Li, Chunyang; Ma, Kaiyang; Hu, Xindi; Feng, Jin
Abstract: In this work, an angiotensin converting enzyme (ACE) inhibitory peptide from loach, Ala-His-Leu-Leu (AHLL), was incorporated into horse spleen apoferritin (HSF) nanoparticles by a disassembly/reconstitute approach. AHLL-loaded HSF nanoparticles displayed a hydrodynamic diameter of about 20 nm and encapsulation efficiency (EE) of about 55%. Sodium deoxycholate (NaDC) of 0.2 mM caused the aggregation of HSF nanoparticles and improved the EE of AHLL. Compared with HSF nanoparticles, NaDC-coated HSF nanoparticles (HSF@NaDC) were more efficient in reducing AHLL degradation in accelerated models and simulated digestion tract owing to their more compact structure. In this regard, the bioactivities of AHLL were better maintained in HSF@NaDC nanoparticles. HSF nanoparticle encapsulation improved the apparent permeability coefficients ( P app ) of AHLL due to the caveolae-related endocytosis. On the other hand, two additional pathways, macropinocytosis-mediated and clathrin- and caveolae-independent routes, were involved in internalized of HSF@NaDC nanoparticles, resulting in an even higher P app value of the loaded AHLL. Graphical abstract: Image 1 Highlights: The disassembly/reconstitute process of ferritin enabled the incorporation of AHLL. Sodium deoxycholate of 0.2 mM caused the aggregation of ferritin nanoparticles. Sodium deoxycholate decoration contributed to the stability of the loaded AHLL. Nanoencapsulation enhanced the intestinal permeability of AHLL. Multiple endocytosis mechanisms were involved in coated nanoparticle absorption.